Therapeutic alternatives for the treatment of melasma: literature review - Kercher, Daiane; Girardi, Bruna Amanda; Viero, Fernanda Tibolla (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No 75 (2022): jul./dez., 2022)
Melasma is a dermatosis that is characterized by the appearance of dark or brownish patches on the skin, its diagnosis is carried out through a specialized evaluation in conjunction with a skin examination using the Wood's Lamp. Thus, the objective of the present project was to carry out a literature review with searches in scientific articles between the years 2012 and 2022, in order to analyze the types of melasma, available treatments, effectiveness of these treatments, possible complementary supplements in the treatment of melasma, guide and provide information about the subject, as well as present studies related to the topic of this article. Among the studies discussed, there is a study in 2016, which was carried out for 60 days with a female patient, using the combination of antioxidants, topical and oral sunscreen for the treatment of melasma, which was successful in lightening hyperpigmentation, in addition to skin rejuvenation. Furthermore, in 2020, a study used a treatment protocol with ascorbic acid and food supplementation that took place for 8 weeks in female volunteers with melasma. At the end of the treatment, they reported lightening of the patches, improvement of expression lines and improvement in the appearance of the skin. Due to the aforementioned facts, it is concluded that the association of the oral use of food supplements with antioxidants, sunscreen and aesthetic treatments, result in a positive impact on the permanent improvement of melasma patches.